Formative assessment and its contribution to the improvement of reading comprehension in a public school in Lima - Bellido-García, Roberto; Lozano-Gonzales, Betty; Cruzata-Martínez, Alejandro; Rodríguez-Huamán, Marco; Rejas-Borjas, Gerardo (European Public & Social Innovation Review, 2025)
Introduction: Formative assessment is an important factor in the prediction and promotion of reading comprehension in the school environment. This would be a consequence of the fact that it increases motivation and commitment to reading, facilitates the adjustment of teaching to the peculiarities of the student and the development of self-regulation skills in reading. Methodology: It is a quantitative, causal correlational methodological design with very high reliability instruments: 0,885 and 0,909, for formative assessment and reading comprehension, respectively. Results: It was found that formative assessment has a significant impact on reading comprehension. Discussions: Contrasting studies have shown that collaboration, motivation and curricular adaptation are favored. Nevertheless, several of them were indirect antecedents. Conclusions: This evaluative strategy fosters self-regulation and autonomy so that students can adjust their learning as a process tailored to their abilities and pace of progress. It provides teachers with didactic tools to adapt their teaching according to the particular needs of the students. It also offers identification of areas of strengths and limitations, timely feedback and collaborative dialogue between educators and learners.